Interactional analysis of mathematics instructional objectives in some selected secondary schools in Oke-ogun, Oyo state (2016)
This study investigated the relative effectiveness of interaction analysis on inter rater scores of the trained observers on students readiness to mathematics instructional objectives in some selected secondary schools in Oke-ogun area, Oyo state, Nigeria. The sample used for the study consisted of senior secondary school students II and teachers' of mathematics in selected secondary schools. Seven hundred and Seventy-five students’ and eighteen mathematics teachers' scores observed under mathematics instructional objectives for senior secondary school class II students were used baser! on receiving, responding, valuing, organization and characterization by a Value or Value Complex for the students and mastery of learning for the mathematics; teachers and level of interaction during teaching-learning process for both the teachers and the students by two-raters for eight weeks were used for the study. To examine the extent to which the inter rater scores influence the result of the exercise, Scott Reliability formular was used. Results showed that the reliability coefficient are r = 0.86, 0.65 and 0.73 for learners' readiness, teachers' mastery of subject area and teacher-student interaction respectively. These results showed that the two raters ' scores are relatively close. It is recommended that students should take their lesson seriously and stake holders responsible for recruitment of teachers should recruited qualified and competent teachers. The mathematics teachers should try their best to carry students along during teaching-learning exercise and students should pay rapt attention to what the teacher teaches. The mathematics teachers should be granted in-service training that would quip them with new pedagogy in teaching-learning and classroom management processes